2013
DOI: 10.1007/s11111-013-0198-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of population, age structure, and urbanization on carbon emissions/energy consumption: evidence from macro-level, cross-country analyses

Abstract: This review summarizes the evidence from cross-country, macro-level studies on the way demographic factors and processes-specifically, population, age structure, household size, urbanization, and population density-influence carbon emissions and energy consumption. Analyses employing time-variant data have produced great variance in population elasticity estimations-sometimes significantly greater than one, sometimes significantly less than one; whereas, cross-sectional analyses typically have estimated popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
164
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 317 publications
(170 citation statements)
references
References 62 publications
3
164
0
3
Order By: Relevance
“…Additionally, less developed regions will account for most of the population growth expected in urban areas. While the impact of urbanization on the environment has been studied (e.g., see [2] for a review), understanding regarding the poverty-urbanization relationship is lacking [3]. Yet, those two forces-poverty and urbanization-are apparent causes for the lack of achieving sustainable development [3].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, less developed regions will account for most of the population growth expected in urban areas. While the impact of urbanization on the environment has been studied (e.g., see [2] for a review), understanding regarding the poverty-urbanization relationship is lacking [3]. Yet, those two forces-poverty and urbanization-are apparent causes for the lack of achieving sustainable development [3].…”
Section: Introductionmentioning
confidence: 99%
“…And the effects of GDP, urbanization rate, 0-14-year-old children's ratio on the emission of carbon monoxide (CO), nitrogen oxides (NOx) and volatile organic compounds (VOC) in European Union countries in 1995-2005 were analyzed. Brantley [31] summarized the literatures, which used the STIRPAT model to study the impacts of total population, age structure, family size and urbanization rate on carbon emissions. This paper summarizes the methods, conclusions, and limitations of existing studies as presented in Table 1.…”
Section: Study Of the Factors Influencing The Consumption Carbon Emismentioning
confidence: 99%
“…Contrary to the former three models, the regression coefficient of regional population urban and rural structure (urban) was negative, and it showed 10% significance, indicated that development of urbanization would reduce the consumption inhibitory factor effect (∆C ci f ). Although the development of urbanization has promoted the rising of the urban population, and increased the amount of residents' consumption, the residents' consumption ratio in provinces of China decreased continuously during the sample period according to the data of the China Statistical Yearbook [43]. Therefore, the contribution of urbanization development on the overall economy was stronger than on residents' consumption.…”
Section: Gdp´4mentioning
confidence: 99%
“…Although some literature considered the effect of population scale change, population structure change, and change of population age structure on carbon emission [43,44], most literature still ignored the effect of population sex structure change and population education and occupation structure change mentioned previously. In addition, although the positive effect of increasing the size and level of consumption on carbon emission has become a consensus, there were few studies related to the effect of change of consumption structure on carbon emission.…”
Section: Literature Reviewmentioning
confidence: 99%